Blood Pressure Variability and Morning Blood Pressure Surge in Elderly Chinese Hypertensive Patients. Issue 7 (29th April 2014) - Qin, Xiaobo; Zhang, Qin; Yang, Suping; Sun, Zhongbo; Chen, Xiaojie; Huang, Huiling
<x xml:space="preserve">Abstract</x> This retrospective study aimed to investigate blood pressure variability (BPV), morning systolic blood pressure surge (MBPS), and the associated factors in 513 elderly (65 years and older) and 188 younger (younger than 65 years) hypertensive Chinese patients who had ambulatory blood pressure monitoring (ABPM) at our hospital from January 1, 2002, to December 31, 2010. The MBPS was lower in the younger patients compared with the elderly patients, and it was highest in the 75 years and older and younger than 80 group (29.0±13.4 mm Hg). Compared with other groups, the 80 years and older group had a significant increase in BPV (P<.05). Multiple linear regression analysis showed that body mass index (BMI; P<.01), up to 50 years of smoking (P≤.03), and circadian blood pressure variation (P<.01) were factors associated with MPBS. In summary, systolic BPV and MBPS were increased in elderly Chinese hypertensive patients, and the MBPS was associated with BMI, years of smoking, and circadian blood pressure variation.